A Facile Strategy to Densify Aligned CNT Films with Significantly Enhanced Thermal Conductivity and Mechanical Strength. Issue 12 (22nd July 2022) - Wu, Yongdong; Ma, Qiangqiang; Liang, Ting; Yao, Yimin; Li, Junhong; Zeng, Xiaoliang; Xu, Jian‐Bin; Sun, Rong
Abstract: Aligned carbon nanotube (CNT) films with outstanding thermal and mechanical properties are promising for thermal management in electronics and mechanical enhancement in composites. One main challenge toward aligned CNT films is the loose stacking and unsatisfactory orientation of individual CNTs within the macroscopic assemblies, resulting in unsatisfactory performance. In this study, a facile strategy to densify commercial aligned CNT films with nearly doubled stacking density increasing from 0.63 to 1.17 g·cm −3, where the densification process involves infiltration of ethanol, CNT protonation along with mechanical stretching, is proposed. The densification strategy makes CNTs compactly aligned at the macro level, and enables CNTs to undergo spatial reorganization at the microscopic level simultaneously, contributing to a 125.9% and 680% enhancement of in‐plane thermal conductivity (357.1 W·m −1 ·K −1 ) and tensile strength (281.7 MPa) in densified CNT films, respectively. The densified CNT films also exhibit synchronous temperature variations with the heat source and excellent reliability in harsh environments, showing great potential in thermal management applications. This study provides effective route for driving commercial CNT films in thermal management, and contributes new ideas for the performance regulation of other carbon‐based macroscopic assemblies. Abstract : A facile and effective densification strategy is developed for commercial aligned carbon nanotube (CNT) films to achieve significantly enhanced thermal conductivity and mechanical strength. The nonequilibrium molecular dynamics simulations further confirm that the improvement mainly originated from the enhanced inter‐tube interaction. Coupled with good reliability, the densified CNT film demonstrates great potential in practical application.